NAGEKEO: ANTARA KENYATAAN DAN HARAPAN MENUJU PERTANIAN YANG BERKELANJUTAN - IMACULATA FATIMA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
Agricultural development in Nagekeo is an expectation of all the people. For this reason thegovernment must work together with the people to design an appropriate plan on agriculturaldevelopment based on principle: indignity, modernity, and sustainablelity for achievingwealthy people. Some ideas that may be considered like: (1) biophysics aspect (maintenancethe soil quality, to improve the land productivity and plant productivity); (2) Irrigationsystem; (3) Exploitation all the soil-water resource; (4) Management dry land with threestrata, agroforestry, and wetland (rice, Azolla, Tiktok, and Fish); (5) To increase networkingsystem; (6) To apply appropriate technology; (7) To develop infrastructure wisely; (8) Tomanage all the information’s based on the need; (9) To empower the economic of the farmersthrough cooperation unit.